ANALYSIS OF GOVERNMENT FINANCIAL PERFORMANCE IN THE VILLAGE INCOME AND EXPENDITURE BUDGET (APBDESA) OF SIX VILLAGES IN MUNGKID DISTRICT BUDGET YEAR 2015-2018 - Akil Akbar Azizi; Mulyanto Mulyanto (MESP–FEB UNS, 2019)
This study aims to determine the financial performance consisting of income performance and expenditure performance. Income performance consists of several ratios, among others, financial independence, effectiveness, efficiency, degree of decentralization and financial dependence. expenditure performance consists of several ratios, including the ratio of operating expenditure, capital expenditure and expenditure efficiency. This type of research is quantitative descriptive. The data collection technique needed in this study is a documentary technique with data in the form of the Realization of Village Revenue and Expenditure Budget (APBDesa) Budget Year 2015 to 2018. The results of this study indicate that the income performance calculated by the independence ratio of six villages in Mungkid District is still relatively low with an average of 16.23% which is included in the instructive criteria. Then the effectiveness is classified as high with an average of 100.16%. The average efficiency ratio is 98.39% which means it is still classified as inefficient. The degree of decentralization is still relatively low with an average of 13.03%. Financial dependence is also still in very high criteria with an average of 86.62%. The expenditure performance analyzed by operating expenditures averaged 50.58% and capital expenditure amounted to 49.41% which indicated that the village still prioritized its budget for operational use compared to capital expenditure used for development. Then seen from the efficiency of expenditure, it is still classified as efficient with an average of 95.84%, which means that the government manages its expenditure budget to be classified as good, by spending its budget not exceeding the budget set.Keywords: Income Performance, Expenditure Performance, Village Budget